2014
DOI: 10.1002/pds.3707
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational study of oseltamivir safety and tolerability in infants and young children ≤24 months

Abstract: Oseltamivir has a good tolerability profile in infants and children aged ≤24 months. These findings contributed to the recent FDA approval of oseltamivir for treating infants aged 2-51 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
(46 reference statements)
1
5
0
Order By: Relevance
“…One of the reported SAEs (diarrhoea) prolonged hospitalization: this event was considered of moderate severity by the investigator, and no treatment was given. The safety profile is consistent with previous findings [20][21][22], and with results of a recent European observational study in 1,065 infants aged 0-24 months with influenza [23], which found similar AE rates in oseltamivir-exposed and unexposed patients (49% versus 55%), suggesting a favourable benefit/risk ratio of oseltamivir treatment in infants [23]. The rates of vomiting and diarrhoea in our study were lower than the respective values of 29 and 35% reported in a clinical trial in 202 children aged 1-3 years who received oseltamivir 30-45 mg twice daily depending on body weight [24].…”
Section: Discussionsupporting
confidence: 91%
“…One of the reported SAEs (diarrhoea) prolonged hospitalization: this event was considered of moderate severity by the investigator, and no treatment was given. The safety profile is consistent with previous findings [20][21][22], and with results of a recent European observational study in 1,065 infants aged 0-24 months with influenza [23], which found similar AE rates in oseltamivir-exposed and unexposed patients (49% versus 55%), suggesting a favourable benefit/risk ratio of oseltamivir treatment in infants [23]. The rates of vomiting and diarrhoea in our study were lower than the respective values of 29 and 35% reported in a clinical trial in 202 children aged 1-3 years who received oseltamivir 30-45 mg twice daily depending on body weight [24].…”
Section: Discussionsupporting
confidence: 91%
“…[9,26]. Gastrointestinal symptoms have been observed in about one in four infants with untreated influenza infection [27]. Of note, nonrespiratory symptoms are not included in most ILI/(S)ARI case definitions [1,28,29].…”
Section: Virus-specific Diagnoses Cannot Be Made Based On Clinical Symptoms Alonementioning
confidence: 99%
“…The efficacy, tolerability, and safety of NA inhibitors for the prevention and management of influenza infections have been demonstrated in large clinical trials that also included infants [ 99 ]. Flu vaccination reduces the incidence of pneumococcal HUS [ 78 ].…”
Section: Therapeutic Management Outcome and Preventionmentioning
confidence: 99%